PygmyBrowse: A Small Screen Tree Browser - Band, Zvi; White, Ryen W. (ACM SIGCHI Conference on Human Factors in Computing Systems (CHI 2006), Montreal, Canada, 2006)
We present PygmyBrowse, a browser that allows users to navigate a tree data structure in a limited amount of display space. A pilot evaluation of PygmyBrowse was conducted, and results suggest that it reduces task completion times and increases user satisfaction over two alternative node-link tree browsers.